2020
DOI: 10.7150/thno.35841
|View full text |Cite
|
Sign up to set email alerts
|

Microglia exacerbate white matter injury via complement C3/C3aR pathway after hypoperfusion

Abstract: Microglial activation participates in white matter injury after cerebral hypoperfusion. However, the underlying mechanism is unclear. Here, we explore whether activated microglia aggravate white matter injury via complement C3-C3aR pathway after chronic cerebral hypoperfusion.Methods: Adult male Sprague-Dawley rats (n = 80) underwent bilateral common carotid artery occlusion for 7, 14, and 28 days. Cerebral vessel density and blood flow were examined by synchrotron radiation angiography and three-dimensional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 46 publications
2
115
0
Order By: Relevance
“…We further showed that microglial activation was secondary to C3aR signaling. Of note, previous studies have implicated complement alternative pathway-activated C3-C3aR signaling in demyelination (33) and neurodegeneration (34). In addition, C1q has been shown to induce axon damage in neurodegeneration (35), bind to a "receptor" in mitochondria (36), and induce neuronal stress (37).…”
Section: Discussionmentioning
confidence: 97%
“…We further showed that microglial activation was secondary to C3aR signaling. Of note, previous studies have implicated complement alternative pathway-activated C3-C3aR signaling in demyelination (33) and neurodegeneration (34). In addition, C1q has been shown to induce axon damage in neurodegeneration (35), bind to a "receptor" in mitochondria (36), and induce neuronal stress (37).…”
Section: Discussionmentioning
confidence: 97%
“…However, the neuroprotective microglial state (surveillance/execution mode) can be disturbed during pathology, causing these cells to shift toward a reactive phenotype. These reactive microglia respond with exacerbated secretion of proinflammatory mediators (Vinuesa et al, 2019) and altered phagocytotic properties (Baik et al, 2019;Zhang et al, 2020).…”
Section: Microgliamentioning
confidence: 99%
“…Third, since this is an imaging study, we focused mainly on the macroscopic changes of brain and did not assume and detect signaling pathways mediating the white matter lesions and microglial activation. In fact, microglial polarization mediated inflammatory and complement pathways contribute to white matter lesions in the VaD model ( Qin et al, 2018 ; Zhang et al, 2020 ). Therefore, the downstream mechanism needs to be addressed in future studies as a next step to clarify the molecular target of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the deep location at non-overlapping regions of cerebral arterioles or capillaries, white matter is vulnerable to the CBF reductions ( Wang et al, 2020 ). White matter lesions caused by ischemia, encompassing axonal damage, loss of myelin-associated glycoproteins, and microglial activation, are common pathological changes in VaD ( Struys et al, 2017 ; Qin et al, 2018 ; Zhang et al, 2020 ). Diffusion tensor imaging (DTI) study reports that VaD patients have a specific pattern of white matter lesions affecting the thalamic radiations or corpus callosum (CC) to a greater extent ( Fu et al, 2012 ; Palesi et al, 2018 ), which appears as decreased fractional anisotropy (FA), increased radial diffusivity (RD), and axial diffusivity (AD) ( Choi et al, 2016 ; Ben-Ari et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%